Factors for the Decline of the Self-employed in Korea: A Search and Matching Model Approach - Jiwoon Kim (KDI Journal of Economic Policy, 2022)
This paper studies potentially relevant factors affecting changes in the number of self-employed in Korea during the period of 1986-2018. The number of self-employed had increased steadily until 2002 but started to decrease around that time and had continued to decline. The increasing trend in the number of self-employed during 1986-2001 is mostly explained by demographic changes, whereas the declining trend during 2002-2018 cannot be explained by demographic factors. In this study, I consider four institutional factors that potentially affect the decrease in the number of self-employed after 2002: i) a decrease in the job-separation rate of wage workers, ii) an increase in the income tax rate applied to the self-employed, iii) an increase in minimum wages, iv) an expansion of unemployment insurance benefits. Using a search and matching model with the self-employed, I quantify the effects of these four factors on the decrease in the number of self-employed during 2002-2018. Quantitative results show that the impact of the increase in the minimum wage is relatively large, whereas the effects of the other three factors are limited. The increase in the minimum wage accounts for approximately 17.5% (0.169 million) of the decrease in the number of self-employed during 2002-2018 (0.964 million).
Keywords: E24; J24; 330; Self-employed; Institutional Factors; Minimum Wages; Occupational Choice